Study of the radiation of the parasite Cryptosporidium in some water sources in Basra Governorate. - غواد, عبدالحسين حبش (University of Thi-Qar Journal of Science, 2014)
This study was done during the period from December 2012 until May 2013. The watersamples were collected from rivers (Shatt-Al-Arab, Robat, Khora, Khandq),sewage water(Al-Asmai, Hay Al-Rafadin and Nadhran), Taps water (Qurna, Karmit Ali, Zabir and Basrah old city) and water treatment plant (Al-Bradai and Karmit Ali ). Modifieds acid fast stain and flotation in saturated sugars solution method were used for diagnosis parasite oocyst.The results of the present study showed that the height concentration of oocyst were in February (119 /litter) and April (147 / litter) and the less concentration were in May (61 / litter) and January/2013 (58 / litter).